2018
DOI: 10.1177/0734242x18777800
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria decision analysis of waste-to-energy technologies for municipal solid waste management in Sultanate of Oman

Abstract: The Sultanate of Oman faces challenges, like rapid growth of waste generation, which calls for an optimum waste management strategy. Oman has witnessed the production of 1.5m t of municipal solid waste in 2012, which is expected to elevate to 1.89m t in 2030. This rapid increase needs to be tackled to reduce the generation rates along with the environmental impacts. Currently, there are no treatment facilities in Oman other than limited recycling, and therefore dumping waste into the landfill is the only ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 46 publications
4
47
0
1
Order By: Relevance
“…An analysis of numerous case studies on waste-to-energy facilities in developing countries was conducted and concluded that waste-to-energy still has potential but is struggling for implementation (Vujic, 2015;Adebe, 2018;Kristiansen, 2018;Qazi et al, 2018). Based on this complete investigation and critical criteria examined, the research study could highlight limiting factors/constraints.…”
Section: Multi-criteria Analysis Of a Developing Countriesmentioning
confidence: 99%
“…An analysis of numerous case studies on waste-to-energy facilities in developing countries was conducted and concluded that waste-to-energy still has potential but is struggling for implementation (Vujic, 2015;Adebe, 2018;Kristiansen, 2018;Qazi et al, 2018). Based on this complete investigation and critical criteria examined, the research study could highlight limiting factors/constraints.…”
Section: Multi-criteria Analysis Of a Developing Countriesmentioning
confidence: 99%
“…Similar results were obtained by De Medina-Salas et al [102] who analyzed the lowest EcC and EnC MSW treatment scenarios and landfilling in a medium-sized city using the ELECTRE Method. In another study by Qazi et al [104], waste to energy options for MSW treatment with the lowest EcC and EnC in Sultanate of Oman were also investigated using the same method and the results indicated that AD is the best scenario for organic fractions of MSW with low EcC and EnC costs. Due to variations in waste quantities and compositions, different cities can have different best scenarios reflecting the conditions of the concerned locality.…”
Section: Environmental and Economic Evaluations Of Msw Treatment Optionsmentioning
confidence: 99%
“…The feasibility of using WtE technologies and the expected effectiveness of establishing WtE plants in GCC countries have been assessed in previous publications. Previous studies of WtE in GCC countries have focused on waste characterization [35][36][37], determining energy recovery potential [23,24,26,38], and selecting suitable WtE technologies [38]. Several methods have been used in the assessments of the waste management practices in GCC countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used in the assessments of the waste management practices in GCC countries. A lifecycle assessment [39] and a driver-pressure-state-impact-response framework [40] have been used in Kuwait, a multicriteria analysis (MCA) has been used in Oman [38], and WtE technologies have been assessed in Saudi Arabia [41,42]. Anaerobic digestion (AD) was found to be the most suitable option for Saudi Arabia because of the large contribution of organic material to MSW in Saudi Arabia [43].…”
Section: Introductionmentioning
confidence: 99%